Review the influence of cash holding on the debt capacity and providing a new model for determination of debt capacity (Case study Tehran Stock Exchange (TSE) listed companies) - parviz piri; Gholamreza Mansourfar; Samaneh Barzegari Sadaghiani (پژوهش‌های تجربی حسابداری, 2017)
Management of internal financial flexibility depends to the use of cash, debt capacity and their interactions in the face of crisis and external shocks. Debt capacity as one of the decisive factors of internal financial flexibility, refers to amount of debt that companies can make in theirs financing resources without encountering difficulties in repaying debts. Study effective factors on the debt capacity as one component of internal financial flexibility is important for any company, because identification of these factors will leads to improvement business performance and companies can have better reaction in counter of unexpected events and investments opportunities. In this research, we examine the influence of cash holding on the debt capacity in 69 companies listed in Tehran Stock (TSE) during 2003 to2012. Our finding indicates that the level of cash holding is one of the most important factors that can affectthe Company's debt capacity. Therefore cash is one of the main factors in the creation of internal financial flexibility and also has an important role in the determining of debt capacity.